Modeling and Simulation of an Adaptive Control Technique with Reference Model for a Power Oscillation Damping POD Using MATLAB (Latakia University Journal -Engineering Sciences Series, 2022)
Conventional feedback controllers are considering commonly used techniques to achieve most control processes .in which the gain is calculated in consistent manner with mathematical model of controlled plant (normal operation conditions), but this controllers don’t give the same performance to all operations conditions because of the variation in process dynamics due to nonlinear actuators, changes in environmental conditions and variation in the character of the disturbances. This requires a reset (adaptive) a gain of this controllers in consistent with new operation conditions,  by use optimization techniques. In this research have been modeling and simulation model reference adaptive control MRAC to achieve control process by use MIT rule adjustment mechanism, to power oscillation damping POD in SMIB system and study its effect on ensuring the desired response of the damper when changing its parameters due to an external  disturbance using Simulink the results showed that the use of MRAC technique maintains the desired response of the damper when changing the transfer function due to external disturbance.